The evaluation of early initiation breastfeeding implementation in dr. Mohammad Hoesin Hospital of Palembang, Indonesia: Complaints and barriers - Bernolian, Nuswil (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Abstract Background: Early Initiation of Breastfeeding (EIB) is a worldwide health demand of both mother and child. EIB programme implementation is the duty and responsibility of all health care practitioners, ranging from executive staff and manager, which haven’t runs well in Dr. Moh. Hoesin hospital. Objective: To identify opportunities and challenges in running the EIB programme in Obstetric Department of Dr. Moh. Hoesin hospital. Method: In this cross sectional study, all of birth mothers and health professionals were included. Samples were selected by purposive sampling. Secondary data were obtained from the questionnaire respondents which have been tested for validity and reliability. Results: During November to December 2016 period, there were 19 (51.3%) patients did EIB while 18 (48.6%) others did not. Most patients in no EIB group had abdominal delivery (p = 0,003) and complained that no EIB policy in operating room. Most of EIB implementers (29 doctors and 14 midwives) stated that EIB were already done well but complained of low level of maternal EIB knowledge and lack of EIB practice support from hospital manager. While managerial staff (n = 12) blaming the EIB implementers worked attitude for this issue. Our study found disintegration EIB implementation between the managerial and implementer staff. Conclusion: Our hospital EIB implementation faces challenges, such no EIB policy in operating room, majority of patients are obstetric referral case with complication and unfit for EIB, managerial staff knowledge of EIB differ greatly, low socialization of EIB regulations and other elements of implementation, patient’s level of knowledge, disintegration between the manager and executive staff causing ambiguity in the implementation of the EIB, and the lack of supervision of EIB implementation in the field. Key words: early initiation of breastfeeding, challenge.